The Wiley handbook of problem-based learning - Moallem, Mahnaz; Hung, Woei; Dabbagh, Nada (Wiley handbooks in education, 2019)
The first book to offer an in-depth exploration of the topic of problem-based learning with contributions from international experts The Wiley Handbook of Problem-Based Learning is the first book of its kind to present a collection of original essays that integrate the research and practice of problem-based learning in one comprehensive volume. With contributions from an international panel of leading scholars, researchers, practitioners and educational and training communities, the handbook is an authoritative, definitive, and contemporary volume that clearly demonstrates the impact and scope of research-based practice in problem-based learning (PBL). After many years of its successful implementation in medical education curricula, problem-based learning is now being emphasized and practiced more widely in K-12, higher education, and other professional fields. The handbook provides timely and stimulating advice and reflection on the theory, research, and practice of PBL. Throughout the book the contributors address the skills needed to implement PBL in the classroom and the need for creating learning environments that are active, collaborative, experiential, motivating and engaging. This important resource: * Addresses the need for a comprehensive resource to problem-based learning research and implementation * Contains contributions from an international panel of experts on the topic * Offers a rich collection of scholarly writings that challenge readers to refresh their knowledge and rethink their assumptions * Takes an inclusive approach that addresses the theory, design, and practice of problem-based learning * Includes guidelines for instructional designers, and implementation and assessment strategies for practitioners Written for academics, students, and practitioners in education, The Wiley Handbook of Problem-Based Learning offers a key resource to the most recent information on the research and practice of problem-based learning.